Effect of Heat Stress on Various Physiological Activities and Especially on Reproductive Performance in Dairy Animals - Nasir, Kamran Ahmad; Ahmad, Sohail; Zaman, Haider; Kazmi, Syeda Umm e Farwa; Jan, Hafiz Aftab; Cheema, Imtiaz Ahmed; Muneer, Muhammad Jafir; Khan, Muhammad Munir; Ahmed, Umair; Khan, Sardar Zarq (Indus Journal of Bioscience Research, 2025)
This study examined the effects of heat stress on the physiological functions and reproductive performance of dairy cows, emphasising the influence of cooling techniques, dietary interventions, and exposure to heat stress. This study employed a randomised controlled trial (RCT) methodology, involving two groups of dairy cows subjected to either heat stress conditions (30–35°C and 70–85% humidity) or thermoneutral settings (18–22°C and 45–55% humidity) conducted at UVAS, Lahore. Both groups received conventional or high-energy foods together with cooling measures (fans, misters, and shade). Physiological indicators, such as cortisol levels, body temperature, and respiration rates, were assessed in conjunction with oestrus cycles, ovulation rates, and pregnancy outcomes. The results indicated that heat stress markedly diminished milk production and reproductive health, characterised by prolonged estrous cycles, decreased ovulation rates, and lower pregnancy rates in the heat stress cohort. Cooling systems and nutritional techniques alleviated certain adverse effects; however, heat stress resulted in inferior outcomes relative to the control group. These results provide significant insights into how integrated management techniques can enhance dairy output and fertility rates under heat-stressed conditions. The research yielded substantial implications for dairy production operations, particularly in tropical and subtropical locations, where heat stress is a considerable issue. Future studies should focus on longitudinal studies regarding the effects of heat stress and genetic adaptation in dairy cattle, in addition to exploring the practical uses of cooling and nutritional therapies.